Under Children's Eyes: Becoming Pious in Tayeb Salih and Pramoedya Ananta Toer Short Stories - Novita Dewi (Al-Jami'ah Research Centre, 2017)
This research seeks to discuss how child characters navigate their interactions with the adults in two short stories set in the predominantly Islamic society of Sudan and Indonesia. It examines Tayeb Salih’s “A Handful of Dates” (1964) and Pramoedya Ananta Toer’s “Circumcision” (1950) by locating both texts in World Literature which is largely Western or Eurocentric. Both short stories belong to the genre of initiation fiction often included in world literature anthologies. This paper argues that both authors help contribute to not only the rethinking of World Literature concept and circulation thereof, but also balanced view of heterogonous, multicultural Muslim society. Using post-Genette focalization theory as conceptual framework, this study finds out that the child narrators play distinct roles as (1) the perceptual focalizer to reveal injustice and frivolity of the adults’ world; (2) the ideological focalizer to make meaning of children’s faith through their relationship with the grown-ups. [Penelitian ini bertujuan membahas bagaimana tokoh anak berinteraksi dengan orang-orang dewasa dalam dua cerita pendek dari negara berpenduduk mayoritas Islam, Sudan dan Indonesia. Karya Tayeb Shalih,